Project Management and Engineering Research, 2014 Selected Papers from the 18th International AEIPRO Congress held in Alcañiz, Spain, in 2014 - Ayuso Muñoz, José Luis; Yagüe Blanco, José Luis; Capuz-Rizo, Salvador F. (Lecture Notes in Management and Industrial Engineering, 2016)
This volume features papers from the 18th International Congress on Project Management and Engineering, held by the University of Zaragoza in collaboration with the Spanish Association of Project Management and Engineering (AEIPRO). It illustrates the state of the art in this emerging area. Readers will discover ways to increase the effectiveness of project engineering as well as the efficiency of project management. The papers, written by international researchers and professionals, cover civil engineering and urban planning, product and process engineering, environmental engineering, energy efficiency and renewable energies, rural development, safety, labor risks and ergonomics, and training in project engineering. Overall, this book contributes to the improvement of project engineering research and enhances the transfer of results to the job of project engineers and project managers around the world. It will appeal to all professionals in the field as well as researchers and teachers involved in the training of future professionals.